2023
DOI: 10.1098/rsif.2023.0389
|View full text |Cite
|
Sign up to set email alerts
|

A systems-level analysis of the mutually antagonistic roles of RKIP and BACH1 in dynamics of cancer cell plasticity

Sai Shyam,
Soundharya Ramu,
Manas Sehgal
et al.

Abstract: Epithelial–mesenchymal transition (EMT) is an important axis of phenotypic plasticity—a hallmark of cancer metastasis. Raf kinase-B inhibitor protein (RKIP) and BTB and CNC homology 1 (BACH1) are reported to influence EMT. In breast cancer, they act antagonistically, but the exact nature of their roles in mediating EMT and associated other axes of plasticity remains unclear. Here, analysing transcriptomic data, we reveal their antagonistic trends in a pan-cancer manner in terms of association with EMT, metabol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Moreover, published studies on let-7 have shown that its loss stimulates cell growth and EMT programs, while its overexpression limits these processes 22,23 . Intriguingly, BACH1 and EZH2 have also been associated with partial EMT in cancer 53,54 , where epithelial cells linger as heterogeneous transitional cells which do not transition into mesenchymal cells but instead exhibit a continuum of epithelial and mesenchymal traits which potentiate migration, inflammation, and tumorigenesis 55 . Lineage tracing and scRNA-seq studies indicate that AT2 transitional cells do not transform into fibroblasts via EMT 1013 ; instead, they adopt a mixed gene expression program characterized by simultaneous expression of epithelial and mesenchymal genes, which influences lung remodeling and ECM deposition 13,56 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, published studies on let-7 have shown that its loss stimulates cell growth and EMT programs, while its overexpression limits these processes 22,23 . Intriguingly, BACH1 and EZH2 have also been associated with partial EMT in cancer 53,54 , where epithelial cells linger as heterogeneous transitional cells which do not transition into mesenchymal cells but instead exhibit a continuum of epithelial and mesenchymal traits which potentiate migration, inflammation, and tumorigenesis 55 . Lineage tracing and scRNA-seq studies indicate that AT2 transitional cells do not transform into fibroblasts via EMT 1013 ; instead, they adopt a mixed gene expression program characterized by simultaneous expression of epithelial and mesenchymal genes, which influences lung remodeling and ECM deposition 13,56 .…”
Section: Discussionmentioning
confidence: 99%